HMCN1 as a conserved biomarker of epithelial–mesenchymal transition: a cross-cancer analysis - Leng, Yuanxi; Liu, Yayun; Zhi, Le (Frontiers in Oncology, 2025)
BackgroundThe extracellular matrix (ECM) critically regulates tumor progression, but the systematic role of its large constituent hemicentin-1 (HMCN1) across cancers remains poorly defined. Although implicated in cell invasion and migration, a comprehensive pan-cancer understanding of HMCN1 is lacking.MethodsWe performed an integrative multi-omics analysis of HMCN1 across 33 cancer types using data from TCGA, GTEx, and CPTAC. Based on prominent functional importance in bone tumors, osteosarcoma was selected for functional validation. In vitro experiments, including knockdown and overexpression, were conducted to assess effects on migration and invasion.ResultsHMCN1 was frequently upregulated in tumors and associated with poor prognosis. Its mutations correlated with genomic instability. HMCN1-high tumors were enriched in inflammatory immune subtypes and exhibited a dysfunctional tumor microenvironment. Pathway analysis consistently linked HMCN1 expression to epithelial-mesenchymal transition (EMT). Functional validation in osteosarcoma confirmed that HMCN1 knockdown suppressed, while its overexpression enhanced, cell migration and invasion through regulation of key EMT markers.ConclusionsThis study identifies HMCN1 as a novel, conserved regulator of EMT and a candidate prognostic biomarker across cancers. The findings in osteosarcoma provide a foundational rationale for developing HMCN1 as a potential therapeutic target.